Competition and waiting times in hospital markets - Brekke, Kurt R. (2007)
This paper studies the impact of hospital competition on waiting times. We use a Salop-type model, with hospitals that diﬀer in (geographical) location and, potentially, waiting time, and two types of patients; high-benefit patients who choose between neighbouring hospitals (competitive segment), and low-benefit patients who decide whether or not to demand treatment from the closest hospital (monopoly segment). Compared with a benchmark case of regulated monopolies, we find that hospital competition leads to longer waiting times in equilibrium if the competitive segment is suﬃciently large. Given a policy regime of hospital competition, the eﬀect of increased competition depends on the parameter of measurement: Lower travelling costs increase waiting times, higher hospital density reduces waiting times, while the eﬀect of a larger competitive segment is ambiguous. We also show that, if the competitive segment is large, hospital competition is socially preferrable to regulated monopolies only if the (regulated) treatment price is suﬃciently high.